2012
DOI: 10.1007/s00436-012-3125-1
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo treatments of Echinococcus granulosus with Huaier aqueous extract and albendazole liposome

Abstract: The aim of this study was to investigate the in vitro and in vivo efficacies of chemotherapy employing albendazole liposome (L-ABZ), Huaier aqueous extract, and a Huaier aqueous extract/L-ABZ combination against Echinococcus granulosus. Protoscolices of E. granulosus were incubated in vitro with the two drugs, either separately or in combination, at the following final concentrations: 2 mg/mL Huaier aqueous extract, 10 μg/mL L-ABZ, and 2 mg/mL Huaier aqueous extract + 10 μg/mL L-ABZ. Huaier aqueous extract and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 20 publications
0
25
0
Order By: Relevance
“…Natural dietary products have been widely and safely consumed over centuries, and preclinical studies suggest that some have potential applications in pharmacology and cancer therapy [ 5 ]. In recent years, Huaier extract has attracted increased attention due to its biological activities, including antitumor [ 6 ], anti-parasite [ 7 ] and immunomodulatory effects [ 8 ]. In our previous studies, we have shown that Huaier extract exerts a strong anti-proliferative effect by inducing caspase-dependent apoptosis, suppressing the estrogen receptor α pathway, and inhibiting angiogenesis in breast cancers [ 9 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Natural dietary products have been widely and safely consumed over centuries, and preclinical studies suggest that some have potential applications in pharmacology and cancer therapy [ 5 ]. In recent years, Huaier extract has attracted increased attention due to its biological activities, including antitumor [ 6 ], anti-parasite [ 7 ] and immunomodulatory effects [ 8 ]. In our previous studies, we have shown that Huaier extract exerts a strong anti-proliferative effect by inducing caspase-dependent apoptosis, suppressing the estrogen receptor α pathway, and inhibiting angiogenesis in breast cancers [ 9 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…If patients for whom surgery is not suitable or they refuse surgery, chemotherapy and puncture are recommended as alternative medication [16] . Inactivation of the scolex with a protoscolicidal agent before surgery is intensely recommended, because the spillage of the cyst contents is a major cause of return [17] .…”
Section: Discussionmentioning
confidence: 99%
“…Inactivation of the scolex with a protoscolicidal agent before surgery is intensely recommended, because the spillage of the cyst contents is a major cause of return [17] . During hydatid cyst surgery protoscolicidal agents used to reduce the risk of spillage of viable protoscolices for surgical success [16] . The benzimidazole derivatives and mebendazole are common drugs presently used for management of hydatids cysts.…”
Section: Discussionmentioning
confidence: 99%
“…Although liposomal ABZ treatment of E . granulosus protoscoleces cultured in vitro only showed a very limited (~20%) effect in viability reduction, intra-gastric administration of the same formulation in mice with secondary hydatidosis was sufficient to prevent cyst development in 17 out of 20 (85%) treated mice [ 101 ]. Unfortunately, pure ABZ was not used as a control in this study, so a direct comparison of the therapeutic effectivities of both compounds was not possible.…”
Section: Introductionmentioning
confidence: 99%